Mechanical Life Cycle Handbook : Good Environmental Design and Manufacturing - Hundal, Mahendra ([Place of publication not identified] : CRC Press, 2001)
This work explains how Design For the Environment (DFE) and Life Cycle Engineering (LCE) processes may be integrated into business and manufacturing practices.
"Explains how Design for the Environment (SFE) and Life Cycle Engineering (LCE) processes may be integrated into business an dmanufacturing practices. Examines major environmental laws and regulations in the U.S. and Europe, qualitative and quantitative analyses of ""green design"" decision variables, and heuristic search programs for a proactive future in ecological improvement." "Explains how Design for the Environment (SFE) and Life Cycle Engineering (LCE) processes may be integrated into business an dmanufacturing practices. Examines major environmental laws and regulations in the U.S. and Europe, qualitative and quantitative analyses of ""green design"" decision variables, and heuristic search programs for a proactive future in ecological improvement."
Part 1 General and introductory: introduction to the DFE/LCA; life cycle assessment -- a synopsis; multi-lifecycle assessment -- an extension of traditional LCA; methodologies -- design for the environment; environmental laws -- USA; legislation and market driven requirements -- European examples. Part 2 Product planning: ecodesign with focus on product structures; decision support for planning eco-effective product systems; the ECODESIGN checklist method -- design assessment and improvements. Part 3 Design and manufacturing: holistic design for environment and market -- methodology and computer support; development of an integrated design environment for ecological product assessment and optimization; the utilization phase as a critical element in ecological design; modelling and control for environmentally conscious design and manufacturing; environmental issues in collaborative design. Part 4 Industrial practice: life cycle assessment -- discussion and industrial applications; life cycle engineering -- a tool for optimising technologies, parts and systems. (Part contents).
OCLC-licensed vendor bibliographic record.
Keywords: Industrial design -- Environmental aspects; Environmental engineering; Product life cycle -- Environmental aspects